Single-party government, Prime Minister psychology, and the diversionary use of force: theory and evidence from the British case. Issue 2 (3rd March 2020) - Foster, Dennis M.; Keller, Jonathan W.
ABSTRACT: This paper develops expectations about the likelihood of diversionary conflict initiation by parliamentary democracies with single-party majoritarian (SPM) governments. While most of the literature on diversion and governmental arrangement claims that SPMs have little incentive and/or limited capacity to execute diversionary gambits, we contend that the structural and environmental impetuses for diversion in such states are in fact largely indeterminate. We posit that the psychological attributes of prime ministers under SPM – in particular, their level of distrust – is the most important predictor of how they view structural and environmental constraints, and thus of whether they will militarily divert from poor economic conditions. Distrustful prime ministers are predisposed to the use of force, will dwell on the costs of economic problems, and fear that co-partisan MPs (especially in the cabinet) have designs on their office. Thus, despite having a legislative majority, these leaders will choose diversionary conflict over economic policy fixes. We conduct a partial test of this hypothesis in the British case from 1945 to 2007, and our analyses provide robust support.